Quality control in sputum microscopy among selected health centers in Manila - Bacudio, Ana Maria A. (2001)
The level of proficiency of the 29 sputum microscopists in the City of Manila and its associated factors was determined. This was done by distributing to the centers "TEST" specimen prepared at the Public Health Laboratory in Quiricada. The microscopists processed and examined the test specimens together with the bulk of samples received by the center. The scheme was blinded and allowed for a more objective way of evaluating the actual performance of the 29 TB microscopists.21 quality control specimen were sent in four batches and 6 out of these were sputum positive. Majority (69.0) of the microscopists correctly identified all 3 positive specimen and 17.2were able to identify all the 6 sputum positive sample. The mean score for the microscopic examination of the 21 quality control specimen was 89. All the smears were collected and graded as to quality of smear size, thickness, evenness and staining. Most of them have satisfactory level of proficiency in smear size, thickness, evenness and majority have above 90score in staining.The accuracy of the microscopists and its relationship with associated factors like training, visual acuity and condition of the microscope was also determined. Based from the findings, they have only marginal bearing on the accuracy of the microscopists.The association between the KAP of the microscopists and their level of proficiency was also determined. In this study, majority of the microscopists (52) have adequate knowledge, 66have good attitude and 93have good laboratory practices. It was found out that 29of those with adequate knowledge got score above 90as compared with 33of those with fairly adequate knowledge, and the difference between them is not statistically significant. (p value=0.56). With regards to accuracy and practices, 19of those with good laboratory practices have accuracy of more than 90as compared to 50of those with fairly good practices. The marginally significant differences between accuracy and KAP may be due to small sample size.In this study every step in sputum microscopy was covered and evaluated and if adapted, quality control in all these aspects may help in the improvement of sputum microscopy work thus improving case finding.
Thesis (Master in Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Sputum microscopy